STRATIFIKASI AL-MAQASID AL-KHAMSAH DAN PENERAPANNYA DALAM AL-DHARURIYAT, AL-HAJJIYAT, AL-TAHSINIYYAT - Nilda Susilawati (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2015)
The Stratification of Al-Maqasid Al-Khamsah and its implementation in Al-Dharuriyat, Al-Hajjiyat, Al-Tahsiniyyat Maqasid syariah is aimed for the benefit of thepeople in his life and the hereafter. The stratifications of maqasid are devided in to threecategories: First, the need of Ad-daruriyyah which is a basic need related to the existance offive principles there are faith, soul, mind, descent, and wealth. Second, the need of al-Hajiyyah which is one of the mode in order to maintain those five basic principles, but theneed of al-Hajiyyah level is below the need of ad-daruriyyah. Third, the need of at-Tasiniyyah, if the third need is unable to be fulfilled it will not threat any of the above fivebasic principles, and also it will not cause an obstacle. The level of this need is only as acomplement. Each levels of maqasid syariah should be performed in according to the need ofhuman.